PERILAKU KEPALA KELUARGA DAN KONDISI FISIK RUMAH PENDERITA DIFTERI DI WILAYAH KERJA PUSKESMAS TAMAN DAN WILAYAH KERJA PUSKESMAS SIDOARJO - Erniati .; Nur Haidah; Iva Rustanti (GEMA LINGKUNGAN KESEHATAN, 2014)
Since 2010-2012 the incidence of diphtheria in Province of East Java have increased.The highest rate of diphtheria incidence occurred in Sidoarjo regency area, at the district of Taman and Sidoarjo. The  purposes of this research describes behavior factors included knowledge, attitude, action physical condition ofpatient covered lighting, humidity, floor type, ventilation and residential Oiriity. This_research using total sampling with sample of family treaO of diphtheria patient and the holne  population as many 15 family heads of diphtheria patient in  2012' The result of reseaich indicating that knowledge of familyhead 80% was not good caused of bustle in working then information about diphtheria does not  gained, attitude 5J,3o/owas not  good because knowledlge about diphtheria still low, andaction 73,3olo less because knowledge and attitude aboutdiphtheria incidence was low. The house physical condition of diphtheria did not ineligible beause of ventilation, humidity, residential density incompatibte with health requirements.Whilethe floor type meet the health standalB. For public healthcenters in Taman and Sidoarjo should be improving their informing activities about health and clean behavior living aswell as increasing DPT (Diphtheria Pertusis Tetanus) immunization coverage for children age 0-15 years old.